15N in tree rings as a bio-indicator of changing nitrogen cycling in tropical forests: an evaluation at three sites using two sampling methods - van der Sleen, Peter; Vlam, Mart; Groenendijk, Peter; Anten, Niels P. R.; Bongers, Frans; Bunyavejchewin, Sarayudh; Hietz, Peter; Pons, Thijs L.; Zuidema, Pieter A. (Frontiers in Plant Science, 2015)
Anthropogenic nitrogen deposition is currently causing a more than twofold increase of reactive nitrogen input over large areas in the tropics. Elevated 15N abundance (δ15N) in the growth rings of some tropical trees has been hypothesized to reflect an increased leaching of 15N-depleted nitrate from the soil following anthropogenic nitrogen deposition over the last decades. To find further evidence for altered nitrogen cycling in tropical forests we measured long-term δ15N values in trees from Bolivia, Cameroon and Thailand. We used two different sampling methods. In the first, wood samples were taken in a conventional way: from the pit to the bark across the stem of 28 large trees (the ‘radial’ method). In the second, δ15N values were compared across a fixed diameter (the ‘fixed-diameter’ method). We sampled 400 trees that differed widely in size, but measured δ15N in the stem around the same diameter (20 cm dbh) in all trees. As a result, the growth rings formed around this diameter differed in age and allowed a comparison of δ15N values over time with an explicit control for the potential size-effects on δ15N values. We found a significant increase of tree-ring δ15N across the stem radius of large trees from Bolivia and Cameroon, but no change in tree-ring δ15N values over time was found in any of the study sites when controlling for tree size. This suggests that radial trends of δ15N values within trees reflect tree ontogeny (size development). However, for the trees from Cameroon and Thailand, a low statistical power in the fixed-diameter method prevents to conclude this with high certainty. For the trees from Bolivia, statistical power in the fixed-diameter method was high, showing that the temporal trend in tree-ring δ15N values in the radial method is primarily caused by tree ontogeny and unlikely by a change in nitrogen cycling. We therefore stress to account for tree size before tree-ring δ15N values can be properly interpreted.